MODEL PEMURIDAN MISI BERDASARKAN EFESUS 4:1-16 - wijayanto, Wahyudi (P3M STT Kristus Alfa Omega, 2022)
Mission discipleship aims to mature the disciples of Christ. One of the signs of maturity is bearing fruit. This study aims to find an online discipleship model based on Ephesians 4:1-16 in the preaching of the Good News conducted by LPMI Semarang. The results of this study are the first to be faithful in giving advice. Second, find the spiritual gifts of each disciple. Third, direct the spiritual gifts of students to carry out Preaching the Good News. Fourth, it provides an understanding that each body of Christ has its own duties and functions.